Paravertebral abscess formation and knee arthritis due to Brucellosis in a patient with rheumatoid arthritis - Duyur, B; Erdem, HR; Ozgocmen, S (Nature Publishing Group, 2001)
Objective: To report a case of Brucellosis causing severe joint and vertebra destruction in a patient with rheumatoid arthritis (RA). Setting: Ankara, Turkey. Case report: A 47-year-old man with a known diagnosis of (RA) for 5 years developed paravertebral and epidural abscesses and vertebral fractures and nerve root compression due to brucellosis. The patient underwent surgery for L3-L4 vertebra stabilisation and medical treatment for knee arthritis. Conclusion: It is important to be aware of the possibility of brucellosis in endemic areas, even among patients with a known diagnosis of RA presenting with clinical pictures that may be confused with a flare-up of the RA itself. Steroids and NSAIDs may have the potential to mask disease manifestations.
Keywords: brucellosis; paravertebral abscess; epidural abscess; rheumatoid arthritis